POPULATION GENETICS STUDY OF THE WHEAT LEAF RUST AGENT PUCCINIA TRITICINA IN DAGESTAN - E. I. Gultyaeva; E. L. Shaydayuk; K. M. Abdullaev (Труды по прикладной ботанике, генетике и селекции, 2018)
Background. Leaf rust (causative agent Puccinia triticina Erikss.) is a harmful disease of wheat, Aegilops and triticale in Dagestan.  Germplasm collections of bread wheat and other Triticum and  Aegilops species are studied every year in the experimental field at  the Dagestan Experimental Station of VIR (DES VIR), and evaluated  for leaf rust resistance. Monitoring of the pathogen's virulence makes it possible to assess the dynamics of the fungus's  variability and correct the results of phytopathological scores  performed in different years. The study of the Derbent population  has a long history, and has been conducted since 1970. The aim of  this work is to analyze the virulence of the P. triticina population in 2008-2017.Materials and methods. Infectious material was represented by  leaves of bread wheat with uredopustules collected in the experimental field of DES VIR in 2008, 2009, 2011, 2014, 2016, and 2017. Populations were cloned to obtain monopustule isolates. For  this and for virulence analysis, the laboratory technique of detached  leaves preserved in the benzimidazole solution was used. In total,  144 isolates were employed in virulence studies: 32 in 2008, 37 in  2009, 14 in 2011, 14 in 2014, 26 in 2016, and 21 in 2017.Results and discussion. The genes Lr9, Lr19, Lr24, Lr28, Lr29, Lr41, Lr42, Lr45, Lr47, Lr50, Lr51, Lr53, and Lr65 were  characterized by high efficiency. This means that wheat samples  protected by these genes will demonstrate high-level resistance in  the fields of southern Dagestan. Variations in virulence frequencies  were recorded in Thatcher lines (Tc) with the genes Lr1, Lr2a, Lr2b,  Lг2с , Lr3a, Lr3bg, Lr15, Lr16, Lr20 and Lr26. Using 20 almost  isogenic Thatcher lines (TcLr), 20 phenotypes (races) of the  pathogen were identified. Indexes of genetic distances (Nei and Fst)  indicated at the changes in the structure of the Derbent population in 2014-2017, when compared with 2008-2011. The long- term dynamics analysis (1970-2017) of P. triticina virulence using 10  TcLr lines revealed certain stability in the Derbent population  structure in 1970-2011 and its changes in the subsequent period.